Peripheral Ossifying Fibroma - Luvizuto, Eloa R. [UNESP]; Silva, Jorge B. G. da [UNESP]; Luvizuto, Gisele C. R. [UNESP]; Pereira, Flavia P. [UNESP]; Faco, Eduardo F. S. [UNESP]; Sedlacek, Paulo [UNESP]; Poi, Wilson Roberto [UNESP] (Lippincott Williams & Wilkins, 2012)
The peripheral ossifying fibroma (POF) is a common gingival growth usually arising from the interdental papilla. The anterior maxilla is the most common location of involvement. The etiology and pathogenesis of POF remains unknown. Some investigators consider it a neoplastic process, whereas others argue that it is a reactive process; in either case, the lesion is thought to arise from cells in the periodontal ligament. Trauma or local irritants, such as dental plaque, calculus, microorganisms, masticatory force, ill-fitting dentures, and poor quality restorations, have been implicated in the etiology of POF. The recommended treatment is the excisional biopsy; however, it can leave a defect if the procedure is not followed by a subepithelial connective tissue graft. The main objective of this article was to present a clinical case of excisional biopsy of a POF followed by a subepithelial connective tissue graft to correct the defect caused by the biopsy. The biopsy defect was satisfactorily repaired, and the lesion has not recurred after 6 years of follow-up.
Keywords: Peripheral ossifying fibroma; connective tissue graft; biopsy